Aspectos microestruturais e texturais dos metassedimentos da formacao eleuterio - Zanardo, A.; De Oliveira, M. A F (My University, 1990)
This work describes the primary and tectonic-metamorphic structures of the Eleuterio Formation, cropping 1 km NW of the village of Eleuterio, State of Sao Paulo. The structural feature have been studied chiefly in low grade metamorphic siltites, arkoses and conglomerates. The textural evolution is marked by fragmentation, clay minerals reaction, pression solution with silica recrystallization, mechanical rotation in minerals, fluid circulation and dissolution, mica beards, the possibily crystallization of biotite and epidote, and so on. The tectonic metamorphic foliation now described is supposed to be formed by simple shear with a possible pure shear component. -English summary
Microstructural and textural features of the metasediments of the Eleuterio Formation
Keywords: Eleuterio Formation; foliation; metamorphic rock; structural analysis; textural evolution; Brazil, Sao Paulo, Eleuterio